2014
DOI: 10.1007/s10973-014-3957-2
|View full text |Cite
|
Sign up to set email alerts
|

The differences in thermal profiles between normal and leukemic cells exposed to anticancer drug evaluated by differential scanning calorimetry

Abstract: Chronic lymphocytic leukemia (CLL) is a heterogenous disease with an imbalance between apoptosis and cell proliferation. Therefore, the main goal in CLL therapy is to induce apoptosis and effectively support this process in transformed B lymphocytes. In the current study, we have compared differential scanning calorimetry (DSC) profiles of nuclei isolated from CLL cells and normal mononuclear cells exposed to cladribine or fludarabine combined with mafosfamide (CM; FM), and additionally to CM combined with mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Moreover, the obtained results also revealed that the decrease (or even loss) of thermal transition at 95±5˚C in thermal scans of nuclear preparations of cll cells, after both in vivo and in vitro drug administration, are attributable to chromatin fragmentation during apoptosis (23,24).…”
Section: Relationship Between In Vitro Drug Sensitivity and Clinical mentioning
confidence: 65%
See 2 more Smart Citations
“…Moreover, the obtained results also revealed that the decrease (or even loss) of thermal transition at 95±5˚C in thermal scans of nuclear preparations of cll cells, after both in vivo and in vitro drug administration, are attributable to chromatin fragmentation during apoptosis (23,24).…”
Section: Relationship Between In Vitro Drug Sensitivity and Clinical mentioning
confidence: 65%
“…it has been reported by our laboratory that an additional thermal transition occurs at 95±5˚C in the DsC profiles of nuclear fraction preparations obtained from the mononuclear cells of patients in an advanced stage of cll, along with the main transition at 83±3˚C characteristic for healthy donors (22,23). Moreover, the obtained results also revealed that the decrease (or even loss) of thermal transition at 95±5˚C in thermal scans of nuclear preparations of cll cells, after both in vivo and in vitro drug administration, are attributable to chromatin fragmentation during apoptosis (23,24).…”
Section: Relationship Between In Vitro Drug Sensitivity and Clinical mentioning
confidence: 74%
See 1 more Smart Citation
“…Considerable differences in leukemic cell reactivity were observed in cell samples incubated with Rit, with the cells appearing resistant to Rit in the stable form of the disease. Previous studies have reported that in progressive CLL, additional thermal transition occurs at ~95±5°C (15,19,20,26,28,29), which decreases in the case of the apoptotic activity. The presence of a thermal transition at 95°C following CLL incubation with ≥1 of the agents indicates that the leukemic cells in the stable form of the disease are resistant to Rit.…”
Section: Resultsmentioning
confidence: 98%
“…Later, differential scanning calorimetry (DSC) studies examined a number of different cancers (melanoma malignum, myeloma, colorectal cancer, cervical cancer, leukemia, etc.) and other diseases (e.g., psoriasis, schizophrenia, chronic obstructive pulmonary disease) revealed significant changes in the plasma thermogram when compared with healthy controls [16][17][18][19][20]. Moreover, examination of DSC data in different clinical stages of cancer patients should observe correlation with stages, with tumor size and the extent of regional or distant metastatic invasion [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%